2022
DOI: 10.11113/sh.v14n2.1847
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis of Depression and Cognitive Distortion Module Among Out-Of-Wedlock Pregnant Adolescents

Abstract: Pregnancy should be an exciting experience and a moment awaited, but it is different for out-of-wedlock pregnancy. Unmarried pregnancy causes a variety of problems especially to the pregnant mother including psychological problems such as depression and cognitive distortion. This study aims to identify the needs of depression and cognitive distortion module that can be used for out-of-wedlock pregnant adolescents at a shelter homes in Malaysia. A total of 42 respondents had participated in this study of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In Malaysia, the study found that Malaysian out-of-wedlock shelters use modules developed by shelter management without systematic research procedures [28]. The study also found that shelters for pregnant women out-of-wedlock in Malaysia emphasize spiritual activities and several other activities [28], [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Malaysia, the study found that Malaysian out-of-wedlock shelters use modules developed by shelter management without systematic research procedures [28]. The study also found that shelters for pregnant women out-of-wedlock in Malaysia emphasize spiritual activities and several other activities [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, the study found that Malaysian out-of-wedlock shelters use modules developed by shelter management without systematic research procedures [28]. The study also found that shelters for pregnant women out-of-wedlock in Malaysia emphasize spiritual activities and several other activities [28], [29]. In general, women's shelters offer a variety of activities such as vocational classes (e.g., sewing and handicrafts), religious classes, outdoor activities, and volunteer works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…research is needed to establish a body of evidence of specific group therapy-based treatment that can guide appropriate intervention for MDD in the adult population. Another study(Zaiden et al 2022) was conducted to identify the needs and effects of Cognitive Behavioural Therapy (CBT) on women with MDD and cognitive distortion. Findings revealed that, in terms of scope, the cognitive model and ideas are very limited.…”
mentioning
confidence: 99%
“…Findings revealed that, in terms of scope, the cognitive model and ideas are very limited. Although CBT is categorised as a directive therapy with the goal of changing thoughts and beliefs, this is not always achieved with forceful treatment approach(Zaiden et al 2022).In addition, a study has Implemented Mindfulness-Based Cognitive Therapy (MBCT) combined with mindfulness-based stress reduction and cognitive behaviour therapy elements for depression among employees(Cladder-Micus et al 2018). According to research findings, eight weeks of MBCT treatment during a relapse of depression reduces the risk of relapse.…”
mentioning
confidence: 99%